1998
DOI: 10.1177/009286159803200223
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Biological Assays to Evaluate Botanicals

Abstract: has adopted four "bench top" bioassays which do not require higher animals to screen and direct the fractionation of botanical extracts in drug discovery ejfons. These are: 1. The brine shrimp lethality test (BST) (a general bioassay), 2. The inhibition of crown gall tumors on discs of potato tubers (an antitumor bioassay), 3. The inhibition of frond proliferation in duckweed (a bioassay for herbicides and plant growth stimulants), and 4. The yellow fever mosquito larvae lethality test (a bioassay for pesticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
361
0
34

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(397 citation statements)
references
References 24 publications
2
361
0
34
Order By: Relevance
“…[39] However, further studies are required to determine whether this is also true for the Syzygium extracts examined in these studies. Toxic antibacterial extracts may still be useful as non-medicinal antibacterial agents (eg.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[39] However, further studies are required to determine whether this is also true for the Syzygium extracts examined in these studies. Toxic antibacterial extracts may still be useful as non-medicinal antibacterial agents (eg.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that toxicity in the A. franciscana bioassay may indicate anti-cancer potential. [39] The toxic Syzygium fruit extracts should therefore also be tested against human cancer cell lines to determine their potential as anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has been presented correlations between the general toxicity with the microcrustacean Artemia salina and the citotoxicity on strains of human cells of solid tumors (Mclaughlin, 1991;Mclaughlin et al, 1998) and activity anti-Trypanosoma cruzi (Zani et al, 1995). It has been shown that there is a very good correlation between the median lethal concentrations (LC 50 ) of plant extracts to brine shrimp larvae and the median lethal doses (LD 50 ) of the same extracts, administered orally in mice (Parra et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This bioassay has good correlation with antioxidant activity and cytotoxic activity in some human cancer cells [41]. The results obtained in the bioassay with Artemia salina indicate that the ethanol extract is more toxic in comparison with the others, because a lower concentration is required to achieve 50% mortality (Table 4).…”
Section: Toxicity Analysismentioning
confidence: 85%